Trauma dan Transformasi Mekanisme Pertahanan Ego: Analisis Psikoanalitik Tokoh Pat dan Tiffany dalam Film Silver Linings Playbook - Mandas, Astrid Lingkan; Mende, Delovina Kezkeren N. (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Psychological trauma constitutes a complex emotional response to experiences that threaten an individual’s psychological integrity. Film serves as a critical medium for representing the dynamics of trauma and recovery, as illustrated in Silver Linings Playbook, which portrays the relational trauma experienced by Pat and Tiffany. This study employs a qualitative approach using content analysis of narrative structures, dialogues, and character behaviors. The analysis is grounded in Freudian psychoanalytic theory, particularly ego defense mechanisms, and Judith Herman’s trauma recovery model. The findings show that both characters initially rely on immature and maladaptive defense mechanisms, such as denial and acting out, in response to psychological distress. As their interpersonal relationship develops, these mechanisms gradually shift toward more adaptive forms, including sublimation. This transformation corresponds with Herman’s three stages of trauma recovery: safety, remembrance and mourning, and reconnection. This study argues that the film not only depicts trauma but also represents a processual model of psychological recovery mediated through supportive relationships. Theoretically, it contributes to film psychology by integrating psychoanalytic and trauma frameworks, offering a more comprehensive understanding of character transformation. Furthermore, it highlights film as a reflective medium capable of capturing both the manifestation and gradual resolution of trauma in a nuanced and dynamic way.